Influence Debt To Equity Ratio and Current Ratio On Profit Growth Of Building Construction Companies Listed On The Indonesian Stock Exchange In 2020 - Widjaja, Ichwan Rahmanu; Marnilin, Feni; Irawan, Rahmat (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The main motive of investors in investing capital into one or several companies is to obtain profits (profit/return). Investors can find out whether the company is able to provide the expected benefits or returns by measuring management performance within the company. When investing, investors can measure financial performance through the profits generated by the company. Profit is the company's main source to maintain its survival. Profit growth is a change in the percentage increase in profits obtained by the company. In this research, the leverage ratios used are the Debt-to-Equity Ratio (DER) and Current Ratio (CR) on Profit Growth. The sample used in this research used a purposive sampling method, namely the annual financial reports of Building Construction Companies on the BEI in 2020 as many as 12 companies. The results of this research show that the Partial Debt to Equity Ratio (DER) has a negative and significant effect on Profit Growth, while the Current Ratio (CR) has a negative and insignificant effect on Profit Growth.   Keywords : Debt to Equity Ratio (THE),Current Ratio (CR), Profit Growth